Penerapan Haar Cascade Classifier Dalam Mendeteksi Kelainan Mata Pada Anak Menggunakan OpenCV - Giesta Rahguna Putri; Muhammad Akbar Maulana (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Eye disorders in children need early detection to prevent serious health problems. However, eye examinations at healthcare centers are currently limited. OpenCV is an image processing library that can detect eye disorders such as strabismus and crossed eyes. Research shows that OpenCV aids in the early detection of eye disorders in children at healthcare centers. Haar Cascade Classifier is an image processing technique used to detect specific objects. It can accurately detect faces under various lighting and background conditions. It serves as an effective alternative for object detection in digital images.